Quaternary ammonium compounds (QACs), QAC resistance genes, and QAC-tolerant bacteria in livestock and human waste streams - Sophie Lennartz; Osas Elizabeth Aigbekaen; Alexandra Jahraus; Jan Siemens; Ines Mulder; Stefanie P. Glaeser (Journal of Hazardous Materials, 2026)

Rapid mineralization of mineral-bound carboxyl-carbon of salicylic acid and phenylalanine - Alexander Konrad; Diana Hofmann; Jan Siemens; Friederike Lang; Ines Mulder; Kenton P. Stutz (Soil Biology and Biochemistry, 2026)

Long-term effects of manure addition on soil organic matter molecular composition: Carbon transformation as a major driver of energetic potential - Carsten Simon; Anja Miltner; Ines Mulder; Klaus Kaiser; Marcel Lorenz; Sören Thiele-Bruhn; Oliver Lechtenfeld (Soil Biology and Biochemistry, 2025)

Microbial carbon use efficiency of mineral-associated organic matter is related to its desorbability - Alexander Konrad; Diana Hofmann; Jan Siemens; Kenton P. Stutz; Friederike Lang; Ines Mulder (Soil Biology and Biochemistry, 2025)

Downstream effects of the pandemic? Spatiotemporal trends of quaternary ammonium compounds in suspended particulate matter of German rivers - Sophie Lennartz; Jan Koschorreck; Bernd Göckener; Karlheinz Weinfurtner; Andrea Frohböse-Körner; Jan Siemens; Sanjana Balachandran; Stefanie P. Glaeser; Ines Mulder (Journal of Hazardous Materials, 2024)

Widespread occurrence of quaternary alkylammonium disinfectants in soils of Hesse, Germany - Kai Jansen; Christian Mohr; Katrin Lügger; Christian Heller; Jan Siemens; Ines Mulder (Science of The Total Environment, 2023)

Biosolids for safe land application: does wastewater treatment plant size matters when considering antibiotics, pollutants, microbiome, mobile genetic elements and associated resistance genes? - Birgit Wolters; Kristin Hauschild; Khald Blau; Ines Mulder; Benjamin Justus Heyde; Søren J. Sørensen; Jan Siemens; Sven Jechalke; Kornelia Smalla; Joseph Nesme (Environmental Microbiology, 2022)
Summary Soil fertilization with wastewater treatment plant (WWTP) biosolids is associated with the introduction of resistance genes (RGs), mobile genetic elements (MGEs) and potentially selective pollutants (antibiotics, heavy metals, disinfectants) into soil. Not much data are available on the parallel analysis of biosolid pollutant contents, RG/MGE abundances and microbial community composition. In the present study, DNA extracted from biosolids taken at 12 WWTPs (two large‐scale, six middle‐scale and four small‐scale plants) was used to determine the abundance of RGs and MGEs via quantitative real‐time PCR and the bacterial and archaeal community composition was assessed by 16S rRNA gene amplicon sequencing. Concentrations of heavy metals, antibiotics, the biocides triclosan, triclocarban and quaternary ammonium compounds (QACs) were measured. Strong and significant correlations were revealed between several target genes and concentrations of Cu, Zn, triclosan, several antibiotics and QACs. Interestingly, the size of the sewage treatment plant (inhabitant equivalents) was negatively correlated with antibiotic concentrations, RGs and MGEs abundances and had little influence on the load of metals and QACs or the microbial community composition. Biosolids from WWTPs with anaerobic treatment and hospitals in their catchment area were associated with a higher abundance of potential opportunistic pathogens and higher concentrations of QACs.

Soil water solutes reduce the critical micelle concentration of quaternary ammonium compounds - Ines Mulder; Malte Schmittdiel; Henning Frei; Laura Hofmann; Dennis Gerbig; Jan Siemens (Environmental Science and Pollution Research, 2020)
Quaternary alkyl ammonium compounds (QAACs) are produced in large quantities for use as surfactants and disinfectants and also found in soils, sediments, and surface waters, where they are potentially involved in the selection of antibiotic resistance genes. Micelle formation influences fate and effects of QAACs. The critical micelle concentration (CMC) of six homologs of benzylalkylammonium chlorides (BAC) was determined in deionized water, 0.01 M CaCl 2 solution, and aqueous soil extracts, using both spectrofluorometric and tensiometric methods. Additionally, eight organic model compounds were employed at concentrations of 15 mg C L −1 as background solutes in order to test the effect of dissolved organic carbon (DOC) on CMCs. Results found CMCs decreased with an increasing length of the alkyl chain from 188 mM for BAC-C8 to 0.1 mM for BAC-C18. Both methods yielded similar results for measurements in water and CaCl 2 solution; however, the spectrofluorescence method did not work for soil extracts due to fluorescence quenching phenomena. In soil extracts, CMCs of BAC-C12 were reduced below 3.7 mM, while the CMC reduction in soil extracts was less pronounced for BAC-C16. Besides ionic strength, molecular structures of BACs and dissolved organic compounds also affected the CMC. The number of carboxyl groups and small molecular weights of the DOC model compounds reduced the CMCs of BAC-C12 and BAC-C16 at pH 6. This study highlights that CMCs can be surpassed in soil solution, pore waters of sediments, or other natural waters even at (small) concentrations of QAACs typically found in the environment.

Quaternary ammonium compounds in soil: implications for antibiotic resistance development - Ines Mulder; Jan Siemens; Valerie Sentek; Wulf Amelung; Kornelia Smalla; Sven Jechalke (Reviews in Environmental Science and Bio/Technology, 2018)

Enrichment for enhanced competitive plant root tip colonizers selects for a new class of biocontrol bacteria - Faina Kamilova; Shamil Validov; Tatiyana Azarova; Ine Mulders; Ben Lugtenberg (Environmental Microbiology, 2005)
Summary Our group studies tomato foot and root rot, a plant disease caused by the fungus Forl ( Fusarium oxysporum f.sp. radicis‐lycopersici ). Several bacteria have been described to be able to control the disease, using different mechanisms. Here we describe a method that enables us to select, after application of a crude rhizobacterial mixture on a sterile seedling, those strains that reach the root tip faster than our best tomato root colonizer tested so far, the Pseudomonas fluorescens biocontrol strain WCS365. Of the five tested new isolates, four appeared to be able to reduce the number of diseased plants. Analysis of one of these strains, P. fluorescens PCL1751, suggests that it controls the disease through the mechanism ‘competition for nutrients and niches’, a mechanism novel for biocontrol bacteria. Moreover, this is the first report describing a method to enrich for biocontrol strains from a crude mixture of rhizobacteria. Another advantage of the method is that four out of five strains do not produce antifungal metabolites, which is preferential for registration as a commercial product.